Climate finance in East Africa - Tallulah Cherry-Virdee; Josephine Nyamai Warunge; Hans Peter Dejgaard (Danish Institute for International Studies (DIIS), 2024)
This working paper analyses the public international climate-related development finance reaching Kenya, Tanzania and Uganda, the three largest countries in the East Africa region, in the period 2015-2022 with a focus on the quantity of and trends in commitments of adaptation-related development finance. The paper also provides an overview of the countries' climatic, economic and sociopolitical contexts including indebtedness and risk of debt distress, climate change projections and impacts and governance for climate change and climate finance. The discussion of the paper contextualises the observed trends in climate and adaptation-related development finance commitments within this overview and leads to five key conclusions regarding the amount of adaptation finance, the degree of devolution, the use of financial instruments and the grant equivalence of climate loans, the level of gender integration and climate finance tracking and reporting.
Keywords: 330; climate finance; development finance; adaptation; Kenya; Tanzania; Uganda; the East African Community; East Africa